THE EFFECT OF COMPETENCE AND MOTIVATION ON ORGANIZATIONAL COMMITMENTS AND ITS IMPLICATIONS ON EMPLOYEE PERFORMANCE - Khoirul Anwar; Muhammad Havidz Aima (Dinasti International Journal of Education Management And Social Science, 2019)
The purpose of this study is to find out and explain the effect of competence and motivation on organizational commitment and its implications for employee performance, which in this case is the performance of the PBC Audit Functional Officer at the Directorate General of Customs and Excise, Ministry of Finance of the Republic of Indonesia. The research method uses a quantitative approach, which became the population in this study were 318 PBC Audit Functional Officers of the Directorate General of Customs and Excise. The selection of sample is done by simple random sampling technique (Slovin 10% error tolerance), so that 77 respondents are determined. Data collection techniques that used are interviews and questionnaire instruments. The questionnaire survey instrument was randomly delivered to the PBC Audit Functional Officer at the Directorate General of Customs and Excise. The data is analyzed using structural equation modeling (SEM) with the Smart PLS 3.0 software program. This study revealed that competence, motivation and commitment organizational had a significant positive effect on employee performance, both partially and simultaneously. Besides that, organizational commitment variable does not mediate competence and motivation variables on employee performance.